Public Commemoration and Ethnocultural Assertion: Winnipeg Celebrates the Diamond Jubilee of Confederation - Cupido, Robert (Urban History Review / Revue d'histoire urbaine, 2010)
The Canada-wide celebration of the Diamond Jubilee of Confederation was intended to promote the idea of a “new nationality” based on the linguistic and cultural dualism associated with Canada’s two “founding races.” The widespread participation of New Canadians in the celebrations was expected to accelerate their assimilation into the “melting pot” of the new nationality, which did not recognize the legitimacy of dual identities and loyalties. Winnipeg’s diverse and marginalized ethnic communities challenged both the official meanings of the Diamond Jubilee and the hegemonic Anglo-conformity of the city’s civic culture. They transformed the celebrations into a vehicle for representing their ethnocultural identities in the public sphere and asserting an alternative, pluralistic version of Canadian nationality. Winnipeg’s Jubilee celebrations became a milestone in an ongoing “dialectic of resistance and accommodation” that allowed immigrant groups to negotiate the terms of their integration into Canadian society, and that continues to structure the relationship between minority and mainstream cultures in the twenty-first century.